Persistent Gingival Bleeding After Scaling: A Diagnostic Clue to von Willebrand Disease - Huihui Zhang; Nan Qiu; Zhengguo Cao; Shuhuan Shang (Clinical Case Reports, 2026)
ABSTRACT Von Willebrand disease (VWD) is not a rare inherited bleeding disorder. However, it is frequently underdiagnosed because early mucocutaneous bleeding manifestations are often attributed to local factors such as inflammation or anatomical abnormalities, leading to delayed recognition of the underlying systemic disease. A 31‐year‐old Han Chinese female presented with persistent gingival bleeding after routine dental scaling. Her medical history was notable for lifelong recurrent epistaxis and severe intraoperative bleeding during a previous cesarean section, both of which had been attributed to local causes. Her father also had a history of childhood epistaxis. Considering the suggestive personal and family bleeding history, the periodontist suspected an underlying systemic bleeding disorder and referred her to a hematologist. Further laboratory and genetic testing confirmed a diagnosis of type 2M/2A VWD, a rare and recently defined subtype. This case highlights two important clinical messages. First, clinical practitioners, including dentists, can serve as key first responders in identifying systemic disorders by carefully evaluating bleeding and family histories rather than focusing solely on local oral conditions. Second, a comprehensive, patient‐centered diagnostic approach is essential to avoid delayed diagnosis of inherited bleeding disorders such as VWD. This case report emphasizes the important role of non‐hematology clinicians in the early diagnosis of rare VWD subtypes.